Experimental shelter-switching shows shelter type alters predation on caterpillars (Hesperiidae). (7th July 2021) - Baer, Christina S; Marquis, Robert J
Abstract: Caterpillars build various shelters that protect them from natural enemies, but whether specific shelters provide different protection is unknown. To disentangle a caterpillar species' shelter from the rest of its phenotype, we performed a field experiment in which two caterpillar species ( Urbanus dorantes and U. proteus ) were removed from their original shelters, placed into shelters made by conspecifics or heterospecifics, and monitored for predation and parasitism. Predation was intense, with 0–48% of caterpillars surviving depending on treatment. Shelter builder identity significantly affected predation independent of occupant identity, with caterpillars placed in U. proteus shelters experiencing higher predation than those in U. dorantes shelters. The effect of shelter builder identity was related to shelter type: shriveled leaf shelters built by U. dorantes had a lower risk of predation than cut-and-fold shelters built by either species. Cut-and-fold shelters built by the two species did not have significantly different shapes. Caterpillar stage also significantly affected predation (mid-instars were more successful than early instars), but caterpillar species identity did not. Surprisingly, parasitism was rare, but both shriveled leaf shelters and cut-and-fold shelters resulted in similar overall caterpillar mortality. The differences in predation and overall mortality between shelter types suggest a trade-off between protection from predators and parasitoids. This experiment demonstrates that shelter type determines the fate of the caterpillar inside, independent of the identity of the caterpillar that built the shelter. This is the first experimental evidence that predation may select for shelter type and associated shelter-building behavior in Lepidoptera. Abstract : Many animals build shelters, but how do shelters protect them? Predators killed fewer caterpillars in enclosed shelters than in more open shelters. Caterpillar species did not affect predation. However, when deaths caused by parasitoid wasps were included, the two shelter types provided similar overall protection to caterpillars. This suggests that parasitoids prefer to attack caterpillars that are protected from predators.